2016
DOI: 10.1111/eci.12597
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyponatremia on nerve conduction and muscle strength

Abstract: Whereas chronic mild-to-moderate hyponatremia has no impact on muscle strength, we demonstrate for the first time an impact of profound hyponatremia on nerve conduction studies. Further studies are needed to ascertain the contribution of these latter results on gait disturbances, propensity to falls and attention deficits associated with hyponatremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…Possibly, as the analysis suggested a correspondence between degree of hyponatremia and chances of normalisation after treatment, a trial with longer duration and consequent correction of hyponatremia would show a beneficial effect of serum sodium normalisation on neurocognitive and neuromuscular function. Accordingly, in the two comparable studies which showed a benefit after serum sodium correction, the time point for the second neuromuscular testing was defined as achievement of normonatremia …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Possibly, as the analysis suggested a correspondence between degree of hyponatremia and chances of normalisation after treatment, a trial with longer duration and consequent correction of hyponatremia would show a beneficial effect of serum sodium normalisation on neurocognitive and neuromuscular function. Accordingly, in the two comparable studies which showed a benefit after serum sodium correction, the time point for the second neuromuscular testing was defined as achievement of normonatremia …”
Section: Discussionmentioning
confidence: 99%
“…Possibly, as the analysis suggested a correspondence between degree of hyponatremia and chances of normalisation after treatment, a trial with longer duration and consequent correction of hyponatremia would show a beneficial effect of serum sodium normalisation on neurocognitive and neuromuscular function. Accordingly, in the two comparable studies which showed a benefit after serum sodium correction, the time point for the second neuromuscular testing was defined as achievement of normonatremia 13,24 T A B L E 3 Descriptive comparison as mean (standard deviation) according to different neuromuscular balance tests with eyes closed: force vector area (cm 2 ), orthostatic power (watts), and external muscle activity (Hz) The major strength of our study is our study design with standardised and computerised measurement methods and reproducible processes, allowing a detailed assessment of hyponatremia associated symptoms as well as neurocognitive and neuromuscular functional impairment. However, our study also has limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…did not observe any signi cant difference in GS when the sodium concentration was increased from 127.7 ± 2.5 mmol/L to 136.1 ± 1.8 mmol/L in humans. (25) Mild hyponatremia itself is correlated with muscle strength but the level of hyponatremia may be more severe, noticeably lower than the cutoff.…”
Section: Discussionmentioning
confidence: 99%